Design an Arduino-Based Heart Rate Measuring Device Using a Pulse Sensor - Rizaldy Khair; Ibrahim (INFOKUM, 2021)
Heart rate / pulse is an important indication in the field of health which is useful as an effective and fast evaluation material and serves to determine the health condition of a person's body. The method of measuring the number of pulses has been used by doctors to determine stress, in this day and age there are still many pulses checked and analyzed manually with the help of a doctor or nurse to be able to find out the condition of the pulse when examined. It is very troublesome if only to check the pulse should require the help of a doctor or nurse. Therefore, the design of a portable heart rate device can replace the performance of a doctor or nurse manually, so that the pulse checker can be monitored by himself using a sensor attached to the finger to help analyze the pulse, so that the results can be known by the examiner by looking directly from the LCD. With the current conditions, the role of experts is so important, so the development of modern tools, especially in biomedical matters for various kinds of diagnoses with the help of tools, can make it easier for examiners to check the condition of their pulse with technology that is increasingly developing at this time. The final project this time aims to develop existing technology with the help of pulse sensors as an analysis medium by connecting them to a microcontroller as a voltage source, as a tool that can analyze the pulse, so from the design of this tool can later help the examiner analyze the condition himself by attaching the sensor to the surface of the finger. With the difference in age in each person, the condition before activity is obtained, which is in the range of 60-100 bpm, as for the difference in test results both before and after the activity depends on the seriousness of the person doing activities.